Scanning Tunneling Microscopy, Voltammetry, and X-ray Photoelectron Spectroscopy Study of the Early Stages of Electrochemical Faceting of Gold (111) in Aqueous Sulfuric and Perchloric Acid - Rodriguez Nieto, Felipe Jorge (2003)
The mechanism of the early stages of the electrochemical faceting of Au(111) in 1 M aqueous sulfuric and 1 M aqueous perchloric acid was investigated, at room temperature, combining voltammetry, scanning tunneling microscopy, and X-ray photoelectronic spectroscopy data. The analysis of the first electro-oxidation scan indicates that the formation of OH- and O-electroadsorbed species is accompanied by 2D clustering. Subsequent electro-oxidation scans involve the participation of deeper Au(111) atom layers. Clustering effects are favored by the presence of specifically adsorbed anions. After the electro-oxidation scan, the subsequent fast electroreduction of OH- and O-adsorbates initially produces spinoidal patterns that disappear by clustering, 2D metal island growth at different lattice levels, coalescence of islands, and 2D Ostwald ripening. This complex mechanism involves the participation of cooperative surface phenomena. Repetitive electro-oxidation/electroreduction potential cycling assists the formation of small 3D crystallites leading to Au(111) surface faceting.